Management Information Systems in Organizational Functions - Meiryani; Deniswara, Kevin; Sugiono, Giri Darijanto; Rusgowanto, Fransisca Hanita (International Journal of Psychosocial Rehabilitation, 2020)
Information systems are very useful for companies or organizations or others. Information Management system has a very important influence for an organization which in this case is a corporate organization. Management Information Systems can support company leaders in making decisions and making plans for the company in the future, and can help companies to compete with other companies in creating and processing resources to become products or services that have not only quantity but also good quality. Without an information system, an organization cannot run effectively and efficiently. Information is a data that has been processed in such a way that it becomes a useful form for people who receive it, from that many positive sides if an organization implements an information system in it.